The Impact of Witchcraft on Talaq: An Analysis From Islamic Perspective and Application in Syariah Courts of Malaysia - Muhammad Zakir Azim Mohd Halim; Mohd Nasir Abd Majid; Tuan Muhamamd Faris Hamzi Tuan Ibrahim (USIM Press, 2024)
In Malaysian culture, witchcraft is not a recent phenomenon. As a result, there is a claim that witchcraft was used to ruin the marriage of husband and wife. Such cases in fact occur as grounds for divorce between husband and wife in Syariah Courts of Malaysia. It has been challenging for the judges to take into consideration and determine the veracity of the claim because there were no specific legal laws as guideline to conduct the claim of witchcraft in divorce. Until this day, the issue has become the discussion of scholars to find a solution to the issue of divorce on the grounds of witchcraft. The objective of this paper to explain witchcraft from Islamic view as well as the opinion of Islamic scholar in determining the ruling of talaq involving this witchcraft. This paper will also discuss how a claim of witchcraft can be proved in a Syariah Court of Malaysia when it’s come to the divorce case. By referring to several cases, this study will analyze Syara's opinion on the ruling of divorce due to witchcraft and to what extent it can be applied as a defense in a divorce case. This study is vital to help judicial institutions in providing fairness and protection to couples who are affected by witchcraft. This study will make cases conduct more orderly and equitable as well as getting proper defense and justice to the spouses.